Is intercultural mediation necessary? An approach from a communications perspective - Ridao Rodrigo, Susana (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
Institutionalized intercultural mediation is expanding as a result of the increase in the number of immigrants in our country. Institutionalized intercultural mediation, which started in the early Nineties in Spain, is understood to mean activities carried out by ONGs and by the social services of the host nation. In line with Giménez (1997: 127), we understand intercultural mediation as a modality within the broader field of mediation. Because of its recent expansion, there is not at present a unique methodology accepted by experts in this field. In this paper, our aims are focused on describing various mediation techniques and the possibility of their application within intercultural contexts